1995
DOI: 10.1074/jbc.270.13.7241
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Major Glycosylphosphatidylinositol Membrane-anchored Glycoprotein from Epimastigote Forms of Trypanosoma cruzi Y-strain

Abstract: We have investigated the structure of the glycosylphosphatidylinositol (GPI) anchor and the O-linked glycan chains of the 40/45-kDa glycoprotein from the cell surface of the protozoan parasite Trypanosoma cruzi. This glycoconjugate is the major acceptor for sialic acid transferred by trans-sialidase of T. cruzi Y-strain, epimastigote form. The GPI anchor was liberated by treatment with hot alkali, and the phosphoinositol-oligosaccharide moiety was characterized and shown to have the following structure. [formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
128
1
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 52 publications
8
128
1
7
Order By: Relevance
“…Biochemical studies have shown that in members of the Trypanosomatidae family the pathway of N-linked oligosaccharide processing of protein is similar to that found in other eukaryotic cells (Parodi et al 1981, 1989, Parodi 1993). However, a novel series of unique O-linked N-acetylglucosamine-containing oligosaccharides have been found in sialoglycoproteins (Previato et al 1994(Previato et al , 1995. It has been assumed, based on the results obtained with mammalian cells, that the Golgi complex of trypanosomatids is involved in the glycosylation process.…”
Section: Isolation Of the Golgi Complexmentioning
confidence: 99%
“…Biochemical studies have shown that in members of the Trypanosomatidae family the pathway of N-linked oligosaccharide processing of protein is similar to that found in other eukaryotic cells (Parodi et al 1981, 1989, Parodi 1993). However, a novel series of unique O-linked N-acetylglucosamine-containing oligosaccharides have been found in sialoglycoproteins (Previato et al 1994(Previato et al , 1995. It has been assumed, based on the results obtained with mammalian cells, that the Golgi complex of trypanosomatids is involved in the glycosylation process.…”
Section: Isolation Of the Golgi Complexmentioning
confidence: 99%
“…These differences have been related to the synthesis of cytokines by macrophages induced by mucins isolated from trypomastigotes, but not by mucins isolated from epimastigotes (van Voorhis 1992, Silva et al 1995, Aliberti et al 1996, Camargo et al 1997. Unusually the glucosamine was 6-O-substituted with 2-aminoethylphosphonate, and 2-aminoethylphosphonate was also present on the third mannose residue distal to glucosamine in the GPI-anchor of the mucin isolated from epimastigotes from the Y strain (Previato et al 1995).…”
Section: Mucinsmentioning
confidence: 99%
“…The first evidence for O-glycosylation of serine and/or threonine in trypanosomal glycoproteins came from studies of T. cruzi GP-25 (5), a glycoprotein corresponding to the C-terminal domain of cruzipain (6). More recently, O-glycosylated mucinlike proteins were demonstrated in metacyclic (7) and cellderived trypomastigotes (8) and in epimastigotes (9,10). Structural analyses have shown that these O-glycans vary between strains and developmental stages (9 -11).…”
mentioning
confidence: 99%
“…The striking feature of these O-glycans is that they are linked to the peptide backbone through an N-acetylglucosamine (GlcNAc) unit, with threonine (Thr) rather than serine (Ser) being the usual site of attachment (10,12). The GlcNAc-Thr core can be extended by addition of Galp, Galf, and sialic acid residues.…”
mentioning
confidence: 99%